Tantangan Manejemen Pelatihan dalam Mengatasi Perbedaan Usia dan Ketersediaan Waktu di Kursus Pelatihan Komputer Alberto - Sani Susanti; Anugrah Setiawan; Rista Triwani; Yuni Naibaho; Astri Conia; Romi Anggun; Imelda Sari (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
Research conducted at LKP ALBERTO found problems or challenges that included time and differences between the students, considering that the students had their own responsibilities. Starting from minors who are still attending formal school, or adults who are already working. Plus, the age difference creates different ways of thinking and understanding. The purpose of this research is to find out the challenges and how Alberto's LKP overcomes challenges so that we can propose suggestions or solutions for the LKP. The method used in this research is an interview method where we get direct views from the LKP on student instructors. The interview results show that effective time management is very important to achieve learning goals, but age differences can also influence the way participants understand and react to lesson material. These findings provide insight into how appropriate time management can increase the effectiveness of learning in LKP by taking into account the needs and characteristics of participants from various age ranges.